Assessing the readiness of sustainability reporting tools (SRTs) for an age-friendly built environment. Issue 2 (1st August 2016) - Siew, Renard Y.J.
Abstract : Purpose: Population ageing is expected to have an increasing impact on the economy and society. In particular, it creates a myriad of challenges for stakeholders in the construction and property sectors. The design of the built environment would now need to consider the requirements of the older population in the community. This paper aims to provide a study on the readiness of mainstream sustainability reporting tools (SRTs) in helping to create an age-friendly built environment. Design/methodology/approach: First, a list of criteria representing the needs of the older community in the built environment is developed based on a rigorous literature survey and is validated with five focus groups. Then, using this list, SRTs are assessed for their age-friendly readiness. Findings: The findings from this study show that not only are there variations across different SRTs but also a majority do not emphasize enough on age-friendly criteria. Research limitations/implications: It is suggested that mainstream SRTs should consider allocating mandatory credits for age-friendly criteria. This would definitely encourage property developers and town planners to consider and plan for the needs of the older population. Originality/value: This paper is original as none of the prior studies have considered assessing the readiness of SRTs in creating an age-friendly built environment.